School Meals Energy and Nutritional Composition According to Age Specific Nutritional Guidelines - Eat Mediterranean Program (P04-154-19). (13th June 2019) - Santos, Mariana Coelho; Rito, Ana Isabel; Dinis, Ana; Rascoa, Carla; Mendes, Sofia; Loureiro, Isabel; Castanheira, Isabel
Abstract: Objectives: Eat Mediterranean (EM), a community-based Public Health Program, was developed with the goal to reduce nutritional inequalities in school children through the promotion Mediterranean Diet, giving priority to the school environment 1 The present study addresses the evaluation of school meals nutritional composition, before and after the intervention of the EM, considering the age-specific nutritional recommendations. Methods: EM was developed in three School Groups in the years 2015/16 (1 st Phase – Diagnostic ) and 2016/17 (2 nd Phase – post-intervention) in a total of 25 schools with all educational levels (pre-school through secondary education) considering ages between 2 and 21 years. The meal components collected were: bread, soup and main course (with salad or cooked vegetables). For this study, ten random schools were selected at each phase representing 60 samples analyzed. Macronutrients, energy and salt contents were determined by internal methods developed and validated by the laboratory and according to European or International Standards EN ISO/IEC 17025 2, 3 . School meals nutritional composition evaluation was performed considering that a lunch meal should contribute 30% of the daily energy intake 4, and by checking the deviations related to the age-specific nutritional recommendations 5 . Results: In the 1st phase, school meals showed a negative deviation for total energy and for carbohydrate content, for the groups 6–10 and 16–21 ages (with and without bread). In contrast, with the exception of the age group of 16–21, protein content presented positive deviations. Regarding salt content, different deviations were observed among the studied age groups being these deviations higher than 40% for the age group of 2–5. In the post-intervention phase, corrections were achieved for total energy and carbohydrate content particularly for the age groups of 2–5 e 6–10, for protein values, the positive deviation was still observed and the salt content decreased for all age groups. The fat content was always within the reference intervals. Conclusions: The EM program has proved to have an overall positive impact on the nutritional quality of the school meals provided. However, the reduction of salt content, the provision of adequate amounts of protein as well as the adjustment of the portion served to the respective age group should be reinforced, adjusted and monitored. Funding Sources: Not applicable.